Formulation and evaluation of floating tablets of niacin for sustained release (Asian Journal of Pharmaceutics (AJP), 2014)
Niacin or nicotinic acid (NA) is used in the treatment of hyperlipidemia. NA immediate release formulation shows undesirable effects like flushing of the face and neck parts. In the present study, NA floating sustained release dosageform was developed to prolong the drug release, to retain the drug delivery system above the site of absorption for the desired period of time, and to reduce the drug release rate compared to conventional formulations in order to minimize the side effects. The preformulation parameters such as flow properties and drug-excipient compatibility studies were performed. The drug excipient compatibility studies were performed using the FTIR study and the results showed that all the polymers used in the study are compatible with the pure drug. The floating sustained release tablets of niacin were prepared by the wet granulation method and the granules were evaluated for various micromeritic properties like bulk density, tapped density, Carr’s Index, Hausner’s ratio, and angle of repose. The tablets were evaluated for post-compressional parameters like average weight, thickness, hardness, friability, swelling index, floating lag time and total floating time, and in vitro drug release studies. All the formulations showed total floating time >20 hr. The concentration of the effervescent agent and theconcentration and type of polymer showed an effect on the floating behavior and drug release. The formulation containing 13% sodium bicarbonate, HPMC (33%) and Eudragit RS PO (4%) showed required drug release up to 20 hr.